Host range and susceptibility to Toxoplasma gondii infection in captive neotropical and Old‐world primates. Issue 4 (20th May 2020) - Paula, Nayara Ferreira de; Dutra, Kateanne Silva; Oliveira, Ayisa Rodrigues de; Santos, Daniel Oliveira dos; Rocha, Cláudia Emanuela Viana; Vitor, Ricardo Wagner de Almeida; Tinoco, Herlandes Penha; Costa, Maria Elvira Loyola Teixeira da; Paixão, Tatiane Alves da; Santos, Renato Lima
Abstract: Background: Toxoplasmosis is an important disease affecting captive non‐human primates. The goal of this study was to assess the seroprevalence and pathological findings of toxoplasmosis in different species of captive primates. Methods: Six captive neotropical primates died naturally due to Toxoplasma gondii infection and were necropsied. Tissue samples were evaluated by histopathology and immunohistochemistry. Serum samples from 57 captive neotropical and Old‐world primates housed at the Belo Horizonte zoological garden were analyzed by indirect fluorescent antibody test (IFAT), enzyme‐linked immunosorbent assay (ELISA), and indirect hemagglutination assay (IHA). Results: Neotropical primates had lesions compatible with toxoplasmosis with immunolabeled intralesional T gondii . All Old‐World primates (10/10), but only three neotropical primates (3/47), all belonging to the Sapajus apella species (3/6), were serologically positive. Conclusions: Our results suggest a higher susceptibility of neotropical primates to toxoplasmosis. However, this study also supports the hypothesis that Sapajus apella may be naturally resistant.